Z historii działań politycznych Edvarda Beneša wobec władz brytyjskich (marzec 1939 – lipiec 1940) - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 2002)
Dr. Edvard Beneš the last president of the First Czechoslovak Republic decided to left the country and went on exile just after the München agreement in September 1938. He hoped to be able to act on behalf of the restoration of Czechoslovakia. Still some possibility for his political activity were open not earlier than after March 15th 1939 when the Germans had entranced Prague thus having crushed the München agreement. From the very beginning he aimed to create a kind of Czechoslovak Government in exile and if possible to reconstruct the entire political structure of the Czechoslovak state temporary abroad. He sustained the First Czechoslovak Republic was still existing and according to it’s constitution and it’s law had never ceased to exist. There were however some obstacles that disturbed him and his political supporters to achieved those aims. At first there was disunion in the ranks o f the Czechoslovak emigration as regards the person who ought to be a leader. Beneš was supported by those from USA and Great Britain, and the British Government as well. But there were the other pretenders – Milan Hodża and Stefan Osusky both were Slovac politicians supported by the French government and those Slovacs on exile who wanted the wider autonomy of their country within the framework of the Czecho-Slovak state. Denes refused both as he wanted neither to share the power with the other person nor to accept the equal relation with the Slovacs in their common Czechoslovak state. Eventually there were the war’s events that helped him to solve the most difficult problems. After the outbreak of the War World II he proclaimed Czechoslovakia to be at war with Germany. Still the Allied Powers refused to recognise Czechoslovak government and Great Britain recognised the Czechoslovak National Committee no t earlier than in December 1939. Beneš had to wait till July 1940 when the military catas trophe of France destroyed the political position of his opponents. Still even than however the British had announced the recognition of the so called Provisional Government of the Czechoslovak Republic, they refused to admit the uninterrupted existence of the Czechoslovak state and the recognition of its former borders as well. These were the problems Beneš was forced to deal with for the wartime years to come still since then enjoying the position of an unquestionable leader of the Czechoslovak political emigration during the World War II.